Depressive Symptomatology in Children and Adolescents with Chronic Renal Insufficiency Undergoing Chronic Dialysis - Edith G. Hernandez; Reyner Loza; Horacio Vargas; Mercedes F. Jara (International Journal of Nephrology)
This paper presents a descriptive study, using the Birleson Scale to determine the frequency of depressive symptomatology in children and adolescents with chronic renal insufficiency (CRI) undergoing hemodialysis (HD) and chronic peritoneal dialysis (CPD). There were 67 patients (40 female and 27 male) with a mean age of 14.76±2.71 years, duration of illness ≥3 months, 43 (64.18%) patients with CPD and 24 (35.82%) undergoing HD. The frequency of high occurrence, low occurrence, and absence of depressive symptomatology was 10.45% (𝑛=7), 43.28% (𝑛=29), and 46.27% (𝑛=31), respectively; all of the seven (100%) patients with high occurrence of depressive symptomatology were female (𝑃=0.04), and none of these (0%) had a friend to confide in (𝑃=0.03). Depressive symptomatology in patients with CPD was associated with a lower weekly 𝐾𝑡/𝑉 compared to those without depressive symptomatology (2.15±0.68 versus 2.52±0.65; 𝑃=0.01). There was no association with patient age, caregiver, time and dialysis type, anemia, bone disease, nutritional or financial status, origin, schooling, or employment.